Importance of Translocon Subunit Tic56 for rRNA Processing and Chloroplast Ribosome Assembly. Issue 4 (12th October 2016) - Köhler, Daniel; Helm, Stefan; Agne, Birgit; Baginsky, Sacha
Abstract : A defect in Arabidopsis chloroplast translation causes an albino phenotype of the plastid protein import mutants tic56-1 and ppi2 (toc159). Abstract: Toc159-containing complexes at the outer chloroplast envelope membrane form stable supercomplexes with a 1-MD translocon at the inner chloroplast envelope membrane of which Tic56 is one essential subunit. While the single mutants tic56-1 and ppi2 ( toc159 ) have an albino phenotype and are able to grow heterotrophically, we find the double mutant to be embryo lethal. Comprehensive quantitative proteome profiling with both single mutants in combination with GeneChip analyses identified a posttranscriptional defect in the accumulation of plastid ribosomal proteins and diminished expression of plastid encoded proteins. In the tic56-1 mutant, the assembly of functional ribosomes is furthermore hampered by a processing defect of the plastid 23S rRNA. Spectinomycin-treatment of wild-type plants phenocopies the molecular phenotype of plastid proteome accumulation in tic56-1 and to a smaller degree also ppi2 plastids, suggesting that a defect in plastid translation is largely responsible for the phenotype of both import mutants. Import experiments with the tic56-3 mutant revealed no significant defect in the import of small ribosomal protein 16 in the absence of full-length Tic56, suggesting that the defect in ribosome assembly in tic56-1 may be independent of a function of Tic56 in protein import. Our data establish a previously unknown link between plastid protein import, the processing of plastid rRNAs, and the assembly of plastid ribosomes and provide further knowledge on the function of the translocon components and the molecular basis for their albino phenotype.